13. Safety investigation of “Thong Ta Yeu Phuong” capsules: Assessment of acute and subchronic toxicity in the experiment - Phu, Le Hong; Thuc, Nguyen Cong; Hang, Dinh Thi Thu (Tạp chí Nghiên cứu Y học, 2024)
“Thong ta yeu phuong” capsules contained natural materials including Atractylodes macrocephala Koidz., Paeonia lactiflora Pall., Pericarpium Citri Reticulatae, and Ligusticum brachylobum Franch. “Thong ta yeu phuong” capsules were intended to support treating gastrointestinal disorders. So far, the safety of this product, however, has not yet beenreported. Thus, this study aimed to investigate the acute and subchronic toxicities of “Thong ta yeu phuong” capsules through oral administration in experimental animals. The acute toxicity was determined using the Litchfield Wilcoxon method in mice. Following WHO's recommendation, the subchronic toxicity was assessed in rabbits with oral doses of 0.28 g/kg/day and 0.84 g/kg/day for 4 consecutive weeks. In the acute toxicity test, mice given an administration of “Thong ta yeu phuong” capsules at the highest dose (60.0 g/kg) showed no abnormal sign or death. In terms of the subchronic toxicity test, after oral administration of “Thong ta yeu phuong” capsules, hematological parameters and liver function were unchanged as compared with the control group, and no gross lesions in organs were observed in all experimental animals. However, “Thong ta yeu phuong” capsules caused a significant increase in the creatinine level after 4 weeks of treatment. Hence, in clinical practice, “Thong ta yeu phuong” capsules should be used with caution if taken for a long time because of their impact on the function of the kidney.